Morphofunctional Changes in the Gastric Mucosa in the Dynamics of Physiological Pregnancy - E. , Nazarova D.; I. , Parvizi N. (Central Asian Journal of Medical and Natural Science, 2023)
It is well known that during pregnancy there are often clinical signs of disorders of the gastrointestinal tract. Almost all pregnant women complain of certain disorders of the function of the stomach. It is no coincidence, therefore, that the appearance of such symptoms as nausea, vomiting, heartburn, once a perversion ate food in practically healthy women of reproductive age with a delay in menstruation is often used as an indirect sign of pregnancy and is regarded as a normal condition of pregnancy. In all likelihood, these manifestations are associated with certain dynamic functional and morphological changes in the stomach and all parts of the gastrointestinal tract.